2013
DOI: 10.1103/physreve.88.062915
|View full text |Cite
|
Sign up to set email alerts
|

Clustering in delay-coupled smooth and relaxational chemical oscillators

Abstract: We investigate cluster synchronization in networks of nonlinear systems with time-delayed coupling. Using a generic model for a system close to the Hopf bifurcation, we predict the order of appearance of different cluster states and their corresponding common frequencies depending upon coupling delay. We may tune the delay time in order to ensure the existence and stability of a specific cluster state. We qualitatively and quantitatively confirm these results in experiments with chemical oscillators. The exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…This chapter closely mirrors our recently accepted paper with Eckehard Schöll's group [69]. Here, we select sets of four oscillators from the whole population of 64; we apply time-delayed coupling to induce phase locking.…”
Section: Notes To the Readermentioning
confidence: 97%
See 4 more Smart Citations
“…This chapter closely mirrors our recently accepted paper with Eckehard Schöll's group [69]. Here, we select sets of four oscillators from the whole population of 64; we apply time-delayed coupling to induce phase locking.…”
Section: Notes To the Readermentioning
confidence: 97%
“…Ref. [69] demonstrated that, given knowledge of the interaction function, we can accurately predict clustering on networks of such oscillators. In principle, we are able to engineer the radial interaction function now that we have connected stimulation and behavior.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations